Investigating the adverse respiratory effects of beta-blocker treatment: six years of prospective longitudinal data in a cohort with cardiac disease - Cochrane, B.; Quinn, S.; Walters, H.; Young, I. (Internal medicine journal, 2012)
Background:  Globally, cardiovascular disease (CVD) is the leading cause of death. Beta‐blocker medications have well‐established survival benefit for myocardial infarction and heart failure. However, CVD frequently coexists with chronic obstructive airways disease (COPD), a disease in which beta‐blockers are traditionally avoided. Aim:  We sought to investigate the adverse respiratory effects associated with long‐term beta‐blocker treatment in patients with cardiac disease, and presumed high risk of COPD. Methods:  In this prospective cohort study, patients admitted with acute cardiac disease were recruited from the cardiology unit of a tertiary referral hospital. The treating cardiologist determined beta‐blocker treatment, independent of the study. Repeated measures of spirometry and respiratory symptom scores were assessed over 12 months. Respiratory exacerbations, cardiac events and survival were recorded over 6 years. Outcomes were compared according to beta‐blocker exposure. Results:  Sixty‐four subjects participated, 30 of whom received beta‐blockers. Beta‐blockers did not adversely affect spirometry, respiratory symptoms or survival. However, considering two categories of respiratory exacerbations (symptom‐based vs treated), subjects taking beta‐blockers accumulated increased annual risk (relative risk (RR) 1.30, 95% confidence interval (CI) 1.11–1.53, P= 0.001 and RR 1.37, 95% CI 1.09–1.72, P= 0.008) and concluded with overall increased risk (RR 3.67, 95% CI 1.65–8.18, P= 0.001 and RR 4.03, 95% CI 1.26–12.9, P= 0.019), when compared with the group not taking beta‐blockers. Conclusion:  Long‐term beta‐blocker treatment did not adversely affect lung function, respiratory symptom scores or survival, but was associated with increased risk of respiratory exacerbations.